Implementation of a centralized pharmacovigilance system in academic pan-European clinical trials: Experience from EU-Response and conect4children consortia. - Terzić, Vida; Levoyer, Léa; Figarella, Mélanie; Mercier, Noémie; De Gastines, Lucie; Gibowski, Séverine; Demotes, Jacques; Arribas, José Ramón; Mentré, France; Costagliola, Dominique; Røttingen, John Arne; O'Leary, Jackie; et al. (British Journal of Clinical Pharmacology, 2023)
Setting-up a high quality, compliant and efficient pharmacovigilance (PV) system in multi-country clinical trials can be more challenging for academic sponsors than for companies. To ensure the safety of all participants in academic studies and that the PV system fulfils all regulations, we set up a centralized PV system that allows sponsors to delegate work on PV. This initiative was put in practice by our Inserm-ANRS MIE PV department in two distinct multinational European consortia with 19 participating countries: conect4children (c4c) for paediatrics research and EU-Response for Covid-19 platform trials. The centralized PV system consists of some key procedures to harmonize the complex safety processes, creation of a local safety officer (LSO) network and centralization of all safety activities. The key procedures described the safety management plan for each trial and how tasks were shared and delegated between all stakeholders. Processing of serious adverse events (SAEs) in a unique database guaranteed the full control of the safety data and continuous evaluation of the risk-benefit ratio. The LSO network participated in efficient regulatory compliance across multiple countries. In total, there were 1312 SAEs in EU-Response and 83 SAEs in c4c in the four trials. We present here the lessons learnt from our experience in four clinical trials. We managed heterogeneous European local requirements and implemented efficient communication with all trial teams. Our approach builds capacity for PV that can be used by multiple academic sponsors.
EVALuna2:551735